THE DEVELOPMENT OF ACCOUNTING IN THE TENT AND AWNING INDUSTRY. - Tische, F. F. (The Accounting Review, 1926)
Abstract National Tent and Awning Manufacturers' Association is a strictly modern invention of about fifteen years of age. Primitive man had to live in tents and in the oriental countries today shops and bazaars are covered with awning. In our modern life over here we seem to think that tents and awnings are not necessities and the business has somewhat deteriorated. In fact, it was in a terrible condition about fifteen years ago. There was a mortality of, perhaps, forty or forty-five per cent of the manufacturers each year going into bankruptcy. There exists perhaps a number of 2200 of what one might call manufacturers in the U.S. today. During the busy season, which is the late spring and early summer, these men know no hours. They are on the job from six o'clock in the morning, perhaps, putting up work, until nine or ten o'clock at night and then they may go in the shop and work until one or two in the morning, trying to get enough work ready to go out and put up the next day. Naturally, with conditions of this kind, where men did not know the value of their service a terrible condition was found as far as prices were concerned. Goods were being sold far below cost, because the mechanics that came into the business had absolutely no conception of what cost meant. They might know the cost of materials, they might know how many hours of labor were put upon a particular job, but when it came to overhead the only thing they saw was the blue sky above.